Odpowiedź:
1) x = - 1/11
2)x = 2/3
3)x = 1/2 =0.5
Szczegółowe wyjaśnienie:
[tex] - \frac{2x - 1}{3} - x = 2x \: \: \: \: \: \: \times 3 \\ - 2x - 1 - 3x = 6x \: \: \: \: \: \: \: \: \: \: \: \: + 2x + 3x \\ - 1 = 11x \\ 11x = - 1 \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \div 11 \\ x = - \frac{1}{11} [/tex]
[tex] - (x + 3)(x - 2) = x(1 - x) \\ - {x}^{2} + 2x + 3x - 6 = x - {x}^{2} \\ 4x = 6 \\ x = \frac{4}{6} = \frac{2}{3} [/tex]
[tex] {2(x + 1)}^{2} = 2x(x + 2) \\ 2 {x}^{2} + 2 = 2 {x}^{2} + 4x \\ 2 = 4x \\ 4x = 2 \\ x = \frac{2}{4} = \frac{1}{2} = 0.5[/tex]